(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Relevance. Necrotizing enterocolitis (NEC) remains one of the most serious causes of morbidity and mortality among premature infants. Despite the progress in neonatology, the incidence of NEC ranges from 1% to 7%, and mortality reaches 20-30%, increasing to 40-60% with surgical intervention. Premature infants with extremely low body weight (<1,500 g) are most susceptible to NEC and require special clinical monitoring. The purpose of the study is to summarize current understanding of risk factors, pathogenesis and diagnosis of NEC, as well as to evaluate the effectiveness of conservative and surgical treatment methods. Materials and methods of research. 40 works published in leading medical journals over the past 15-20 years have been analyzed. The main focus is on the epidemiology of NEC, the role of the microbiome, intestinal ischemia and inflammatory processes, as well as approaches to surgical tactics. The results of the study. It has been established that prematurity leads to poor intestinal motility, impaired mucosal barrier functions and dysbiosis, contributing to the development of NEC. Radiography and ultrasound make it possible to detect characteristic changes in the early stages, including pneumatosis and perforation. Conservative therapy involves temporary cessation of enteral nutrition, infusion support, and antibiotic therapy. In severe forms with perforation, resection of necrotic areas and the application of a stoma are indicated. Conclusions. NEC requires an integrated approach to diagnosis, treatment, and prevention, including the use of breastfeeding and probiotic strategies. Further study of genetic predisposition and optimization of forecasting methods can reduce the risk of complications and increase the survival rate of premature newborns.